ANALISIS NILAI KARAKTER TANGGUNG JAWAB PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 1 BANDUNG TULUNGAGUNG - Feriza Agustin; Frita Asriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is an important part of the learning process in elementary schools, especially in instilling the value of responsibility as a basis for forming students' attitudes and behavior. However, research still found students who have not demonstrated optimal responsible behavior in learning activities. This study aims to analyze the character value of responsibility of students in the subject of Pancasila Education grade IV at SDN 1 Bandung Tulungagung. This study used a qualitative approach with a descriptive research type. The subjects of the study included fourth-grade students and fourth-grade teachers. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the character value of responsibility of students has been evident through the behavior of doing and completing assignments, discipline in participating in learning, compliance with class rules, and concern for the school environment. However, some students were still found to be inconsistent in demonstrating a sense of responsibility, such as late submission of assignments and dependence on help from friends. The conclusion of this study shows that the character value of responsibility has been implemented in Pancasila Education learning, but still needs to be strengthened through continuous habituation and teacher role models.